2001
DOI: 10.1021/cr000019k
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications of Nonmetal Catalysts for Homogeneous Oxidations

Abstract: Nonmetal oxidation catalysts have gained much attention in recent years. The reason for this surge in activity is 2-fold: On one hand, a number of such catalysts has become readily accessible; on the other hand, such catalysts are quite resistant toward self-oxidation and compatible under aerobic and aqueous reaction conditions. In this review, we have focused on five nonmetal catalytic systems which have attained prominence in the oxidation field in view of their efficacy and their potential for future develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
204
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(213 citation statements)
references
References 227 publications
5
204
0
4
Order By: Relevance
“…[4][5][6][7][8][9][10][11] In recent years, a stable class of nitroxyl radicals, 12) as exemplified by 2,2,6,6-tetramethyl piperidinyl 1-oxyl (TEMPO) [(1); Chart 1], has extensively been used as a catalyst for oxidation of alcohols, because TEMPO is readily available from chemical suppliers at a reasonable price, and because the method allows the use of various safe bulk oxidants, thereby offering safe and extremely efficient oxidation of alcohols with considerable operational simplicity. [13][14][15][16][17][18][19][20][21][22][23][24][25] Today, TEMPOcatalyzed alcohol oxidation has high priority not only in academic laboratories, but also in the chemical industries, particularly in the pharmaceutical industry, as an efficient, mild, and environmentally acceptable method.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] In recent years, a stable class of nitroxyl radicals, 12) as exemplified by 2,2,6,6-tetramethyl piperidinyl 1-oxyl (TEMPO) [(1); Chart 1], has extensively been used as a catalyst for oxidation of alcohols, because TEMPO is readily available from chemical suppliers at a reasonable price, and because the method allows the use of various safe bulk oxidants, thereby offering safe and extremely efficient oxidation of alcohols with considerable operational simplicity. [13][14][15][16][17][18][19][20][21][22][23][24][25] Today, TEMPOcatalyzed alcohol oxidation has high priority not only in academic laboratories, but also in the chemical industries, particularly in the pharmaceutical industry, as an efficient, mild, and environmentally acceptable method.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there has been significant interest in using the free radical TEMPO (2,2,6,6-tetramethyl-piperidinyl-1-oxy) or analogues as efficient co-catalysts in the aerobic oxidation of alcohols [26][27][28][29][30][31][32][33]. Sheldon and Reedijk et al have reported the efficient use of copper-bipyridine and copper-pyrazole/TEMPO systems in oxidation reactions under air [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional oxidation methodologies often suffer low chemo-and/or regio-selectivity with low conversion and low turnover number (TON) in an unfriendly way from both economical and environmental aspects which the catalyst is very expensive and generates amounts of hazardous waste. Oxidation reactions catalyzed by both non-metal [7][8] and metal [9][10][11][12][13][14] catalysts have been receiving increasing attention, particularly for the highly selective aerobic oxidations catalyzed by metal complexes [15][16][17]. In nature, aerobic oxidation processes are carried out in a highly selective manner by mono-or dioxygenases under mild conditions [18][19].…”
Section: Introductionmentioning
confidence: 99%